(untitled) (World Bulletin of Social Sciences, 2023)
This article analyzes the issues of studying the work “Musakhkhir albilad” (“Occupation of countries”) by Muhammadyar ibn Arab Katagan by Academician Boriboy Akhmedov.Also, as a result of the analysis and insight of B. Ahmedov’s research, it was revealed that this work is of great source study significance in the study of the geographical location, political, socio-economic (1498-1610) history of Bukhara.